The Influence of Self-Perception on Manipulative Dexterity in Adults with Multiple Sclerosis - Rosa M. Martínez-Piédrola; Cristina García-Bravo; Elisabet Huertas-Hoyas; Patricia Sánchez-Herrera Baeza; Jorge Pérez-Corrales; Carlos Sánchez-Camarero; Marta Pérez- (Hindawi-Wiley, 2021)
Background. Multiple sclerosis is a disorder which causes a loss of functionality, affecting the person's ability to perform activities of daily living, such as interpersonal interactions and relationship, dressing, self-care, or bathing, as well as having a negative impact on work and leisure activities. Aims. This study examined the relationship (correlational or associations/predictive) between self-perceived quality of life and performance of manipulative dexterity. Also, this study sought to measure predictors of dexterity. Study Design. A cross-sectional study from two associations of MS within the Community of Madrid, Spain. Methods and Procedures. A final sample of 30 people with multiple sclerosis. The outcome measures used were the ABILHAND questionnaire, the Purdue Pegboard Test, the Nine Hole Peg Test, and the Box and Block Test. Results. No significant correlations were found between dexterity and self-perception tests; however, correlations were found between perceived dexterity and quality of life (p<0.001). Scores for the ABILHAND questionnaire, which measures the perception of skills in daily living, predicted up to 60% of the variance in the dexterity tests. Conclusions. The results of this study suggest that interventions for improving the manipulative dexterity of people with multiple sclerosis should address the person's perception of improving their manipulative dexterity and the perceived of quality of life, as both factors may influence manipulative dexterity.